Degradation assessment of Vinyl Ester Matrix Fiber Reinforced Plastics Exposed to Cyclic Hydrochloric Acid Concentrations using Gravimetric Analysis for Chemical Storage Tank use - Natasha Dharmakusumah Tania; Kurniawan Winarto; Kubouchi Masatoshi (Journal of Current Scientific Research, 2025)
The roof of an HCl fiber-reinforced plastic (FRP) chemical tank failed by accident after it had been operated for less than its expected lifetime. A possible cause is the change in day and night temperature, which lead to the cyclic change in the concentration of HCl vapor in contact with roof part. To investigate this possibility, a detailed analysis on the durability of the material exposed to cyclic solution concentration is required. In this research, vinyl ester-glass fiber composite specimens were exposed to 35 mass % and 0 mass% of HCl alternately at 40°C to replicate cyclic concentration exposure in both the vapor and liquid phases. The mass uptake and penetration depth of HCl as well as the strength loss of the material were investigated. Mass uptake and thickness change in vapor phase shows two times higher than liquid phase, at 3.5% and 6% respectively. This occurs due to differences in the concentration of solutions that diffuse to the specimen in the vapor phase and liquid phase. This phenomenon arises from variations in the concentration of solutions that diffuse to the specimen in both vapor and liquid phases. The diffusion process is facilitated by osmotic pressure, leading to material swelling and contributing to their degradation. The result of flexural strength measurement of specimens indicated a decreasing trend as exposure time increased. The flexural strength decreases by up to 36% due to plasticization. The Cl and water content profile in specimens that obtained from elemental mapping of cross-sections using Energy-Dispersive X-ray Spectroscopy (EDS) are enhancing the study on how materials degrade, which may be a reason for damage to FRP tank roofs.
Keywords: acid degradation